The Nature, Timing, and Symptom Trajectories of Dropout From Transdiagnostic and Single-Diagnosis Cognitive-Behavioral Therapy for Anxiety Disorders. Issue 6 (November 2021) - Bentley, Kate H.; Cohen, Zachary D.; Kim, Thomas; Bullis, Jacqueline R.; Nauphal, Maya; Cassiello-Robbins, Clair; Sauer-Zavala, Shannon; Sbi, Sophia; Gallagher, Matthew W.; Farchione, Todd J.; Barlow, David H.
Highlights: Dropout from CBT is problematic for patients, providers, and researchers. Better understanding when and why patients drop out from CBT could help prevent it. Participants were most likely to drop out before the start of CBT. Participants most often dropped out due to problems complying with study procedures. Dropouts and completers did not have significantly different symptom trajectories. Abstract: Dropout from psychotherapy is common and can have negative effects for patients, providers, and researchers. A better understanding of when and why patients stop treatment early, as well as actionable factors contributing to dropout, has the potential to prevent it. Here, we examined dropout from a large randomized controlled trial of transdiagnostic versus single-diagnosis cognitive-behavioral treatment (CBT) for patients with anxiety disorders ( n  = 179; Barlow et al., 2017). We aimed to characterize the timing of and reasons for dropout and test whether participants who dropped out had different symptom trajectories than those who completed treatment. Results indicated that overall, the greatest risk of dropout was prior to the first treatment session. In single-diagnosis CBT, dropout risk was particularly elevated before the first session and after other early sessions, whereas in transdiagnostic CBT, dropout risk was low and stable before and during treatment. Participants most often dropped out due to failure to comply with study procedures or dissatisfaction with or desiring alternative treatment. Results from multilevel models showed that trajectories of anxiety symptoms did not significantly differ between dropouts and completers. These findings suggest that there may be specific time windows for targeted and timely interventions to prevent dropout from CBT.